Field reports form for submitting seasonal observations of Iowa birds, Don Priebe, fall 1983 - Phipps, Ruth O.et al; Priebe, Donet al (1983)
An annotated list of birds sighted by Don Priebe submitted by Ruth Phipps. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1983. Epson - sheet feed